Petroleum Derivatives in Iraq The phenomenon of Renewable or Passing crisis - زيارة رحيم حسوني (Journal of Economics and Administrative Sciences, 2012)
Iraq economy suffered, nor , still many difficulties and problems , including oil derivatives crisis that emerged in 2004 and was the most prominent features of the inability of local production to meet the needs of the increasing growth of consumption, the crisis has cast a shadow on the growth of national in general, and citizen living in particular. Therefore, the real test of crisis and challenge to the capacity of government agencies to manage the crisis and control and reduce its harmful effects, which disappear in a region or sector, even begin to appear in another, given the multiplicity and complexity of third-party solution for remedying the negative consequences of deliberate.